Pola Komunikasi dan Informasi Kesehatan Reproduksi antara Ayah dan Remaja - Ekasari, Farida (UI Scholars Hub, 2007)
Masa remaja adalah masa peralihan dari masa anak-anak menuju masa dewasa yang dialami dengan berbagai perubahan fisik dan psikologis. Para remaja berkeinginan kuat untuk mengetahui berbagai perubahan yang terjadi pada diri mereka. Informasi yang diharapkan berasal dari ayah dan ibu tersebut sampai kini masih rendah. Remaja putri yang berdiskusi tentang kesehatan reproduksi dengan orang tuanya 49%, sedangkan remaja putra hanya 13%. Penelitian kuantitatif dengan disain studi cross sectional ini dilakukan di Kecamatan Soreang dan Banjaran, Kabupaten Bandung dengan subyek penelitian adalah ayah yang mempunyai anak remaja benisia 10-19 tahun. Variabel yang diteliti meliputi faktor predisposisi, faktor pemungkin dan faktor penguat. Faktor predisposisi meliputi status pekerjaan ayah, status bekerja ibu, pendidikan ayah, jenis kelamin anak dan pengetahuan kesehatan reproduksi. Faktor pemungkin meliputi waktu kumpul ayah dan anak, pajanan dan media informasi. Faktor penguat meliputi dukungan keluarga dan masyarakat. Penelitian ini menemukan bahwa 51 % responden memperlihatkan pola komunikasi dan pemberian informasi yang kurang. Pada analisis multivariat ditemukan variabel independen yang berhubungan secara bermakna adalah waktu kumpul, dukungan keluarga dan masyarakat. Berdasarkan basil penelitian ini, dilakukan upaya promosi dan sosialisasi kepada ayah dan masyarakat tentang komunikasi dan pemberian informasi kesehatan reproduksi pada anak remaja. Untuk itu, perlu sosialisasi dan informasi tentang cara komunikasi kesehatan reproduksi yang mengutamakan kualitas bukan kuantitas. Adolescence is a period of transition from childhood to adulthood phase marked by changes occurred in both physical and psychological aspect. Therefore, most adolescents are enthusiastic to know those changes in her/his body. It is believed that addressing information about changes and transition occurred in adolescents should begin from the family, particularly from the father or the mother. However, it seems that it is still far from reality. The figure on parents addressing reproductive health information towards their adolescent is low. Percentage of female adolescent who have discussion on reproductive health issues with their parents is about 49%, while percentage of male adolescent is only 13%. The study is quantitative study using cross-sectional study design. The location of the study is at Soreang and Banjaran sub-districts in June, 2006. Subjects of the study are fathers who have adolescent age 10 to 19 years, and number of sample gathered was 100 respondents. Variables studied are: predisposing factors (occupational status of father and mother, father’s educational level, sex, knowledge on reproductive health); enabling factors (time spend with adolescent, and information media exposures); and reinforcing factors (family and society supports). Data were analyzed by univariate, bivariate (chi’s square test) and multivariate (logistic regression test) analyses. The results of the study showed that 51% respondents have poor communication and information pattern. Independent variables which have significant relationship on communication and information pattern were: time spent with adolescent in working day, and family and society support. Multivariate analysis found that the most dominant factor, after controlled by father’s occupation and time spent with adolescent in the working day, is family and society supports. Based on the study result, it is suggested that efforts on promotion and socialization about the importance of communication and reproductive health information addressed to the adolescent, have to be delivered to the father and the community. It is suggested also to inform that it is not only the quantity of communication and information that matters, but also the quality.